Parental beliefs about portion size, not children's own beliefs, predict child BMI. Issue 4 (4th April 2017) - Potter, C.; Ferriday, D.; Griggs, R. L.; Hamilton‐Shield, J. P.; Rogers, P. J.; Brunstrom, J. M.
Summary: Background: Increases in portion size are thought by many to promote obesity in children. However, this relationship remains unclear. Here, we explore the extent to which a child's BMI is predicted both by parental beliefs about their child's ideal and maximum portion size and/or by the child's own beliefs. Methods: Parent–child (5–11 years) dyads ( N  = 217) were recruited from a randomized controlled trial ( n  = 69) and an interactive science centre ( n  = 148). For a range of main meals, parents estimated their child's 'ideal' and 'maximum tolerated' portions. Children completed the same tasks. Results: An association was found between parents' beliefs about their child's ideal ( β  = .34, p  < .001) and maximum tolerated ( β  = .30, p  < .001) portions, and their child's BMI. By contrast, children's self‐reported ideal ( β  = .02, p =  .718) and maximum tolerated ( β  = −.09, p  = .214) portions did not predict their BMI. With increasing child BMI, parents' estimations aligned more closely with their child's own selected portions. Conclusions: Our findings suggest that when a parent selects a smaller portion for their child than their child self‐selects, then the child is less likely to be obese. Therefore, public health measures to prevent obesity might include instructions to parents on appropriate portions for young children.